Effects of tidal charge on magnetic reconnection and energy extraction from spinning braneworld black hole - Wei, Shao-Wen; Wang, Hui-Min; Zhang, Yu-Peng; Liu, Yu-Xiao (Journal of cosmology and astroparticle physics, 2022)
Recent study shows that the magnetic reconnection can serve as an efficient mechanism to extract energy from rapidly spinning black holes. In this paper, we consider the effects of the tidal charge on the energy extraction via the magnetic reconnection in the backgrounds of a spinning braneworld black hole. With the increase of the tidal charge, we find that both the energies of the accelerated plasma and decelerated plasma decrease for the observer located at infinity. To achieve the purpose extracting the net energy from the black hole, the decelerated plasma should take negative energy. Then we observe that the power of the energy extraction via the magnetic reconnection grows with the tidal charge. Meanwhile, the efficiency also increases with the tidal charge indicating that the spinning braneworld black hole with positive tidal charge is more efficient than the Kerr black hole. Compared with the Blandford-Znajek mechanism, the magnetic reconnection process shall have a higher power for positive tidal charge. These results indicate that the tidal charge has a significant effect on the energy extraction via the magnetic reconnection process.